(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
Allowances of increase in professionalism and quality characteristics of the state and local government are analyzed in the article . The current situation and dynamics of personnel capacity of authorities are considered. Measures for increase in a high-quality component of authorities’ personnel are proposed.